Solve: 7(3x + 4) - (3x - 1) = 4(x-4)- 6 (2x - 3)+ 9x.
Answers
Answered by
1
Step-by-step explanation:
first release them as sign...then multiply nd take positive to positive nd then --to ---as sum then finlly u wll get ans.
Attachments:
![](https://hi-static.z-dn.net/files/d09/c2b09379f9c969f8429b460d0520929b.jpg)
Answered by
2
Answer:
21x+28-3x+1=4x-16-12x+18+9x
18x+29=x+2
17x=27
x=27/17
Similar questions
Math,
6 months ago
Hindi,
1 year ago
CBSE BOARD X,
1 year ago
Math,
1 year ago
Chemistry,
1 year ago